Pengaruh Model Pembelajaran Inkuiri Terhadap Kemampuan Menganalisis Unsur Teks Cerita Pendek pada Siswa Kelas XI MIPA SMA YPK Medan Tahun Pembelajaran 2023/2024 - Ramah Atika Siregar; Isthifa Kemal (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to determine the influence of the inquiry learning model on the ability to analyze short story texts by students of grade XI MIPA SMA YPK Medan for the 2023-2024 Academic Year. This study uses a quantitative research method approach. From the results of the research, the author's ability to analyze short story texts before using the inquiry learning model obtained an average score of 66.42 with the highest score of 82 and the lowest score of 50. Meanwhile, the ability to analyze short story texts after using the inquiry learning model obtained an average score of 78.34 with the highest score of 93 and the lowest score of 68. then the tcount value is compared with the ttable with a significant level of a=0.05 (5%) at the degree of magnitude N-1 (35-1=34) and the result is a ttable of 1.7.Thus, the tcount value is greater than the ttable value (29.07), which means that Ha is accepted and Ho is rejected. This study was declared accepted, which means that there is a significant influence on the use of the inquiry learning model by grade XI students of Mipa High School YPK Medan in the 2023/2024 academic year.